2006
DOI: 10.1139/f06-128
|View full text |Cite
|
Sign up to set email alerts
|

Impaired detection of chemical alarm cues by juvenile wild Atlantic salmon (Salmo salar) in a weakly acidic environment

Abstract: Many prey fishes rely on damage-released chemical alarm cues to detect and avoid predators. The ability to use these cues has been shown to confer considerable survival benefits to individuals. While several laboratory studies and a single field study have demonstrated that an ambient pH of 6.0 impairs fishes in their ability to detect these alarm cues, no study had yet compared the response to alarm cue exposures across populations residing in multiple streams of a different acidity level. In our study, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 58 publications
2
41
0
Order By: Relevance
“…5.0-6.0) in fathead minnows and Atlantic salmon (Salmo salar) [38,46]. Under field conditions, experiments revealed a similar absence of response to chemosensory cues in brook trout (Salvelinus fontinalis) and Atlantic salmon exposed to conspecific alarm cues in acidic streams ( pH range; 5.8 -6.3), whereas avoidance responses were retained in neutral pH streams (pH range; 6.8-7.4) [20,45,47,48]. Likewise, episodic acidifying events may cause short-term loss of chemosensory abilities in freshwater fish.…”
Section: Ecological Effects Of Acidification On Olfaction (A) Freshwamentioning
confidence: 91%
“…5.0-6.0) in fathead minnows and Atlantic salmon (Salmo salar) [38,46]. Under field conditions, experiments revealed a similar absence of response to chemosensory cues in brook trout (Salvelinus fontinalis) and Atlantic salmon exposed to conspecific alarm cues in acidic streams ( pH range; 5.8 -6.3), whereas avoidance responses were retained in neutral pH streams (pH range; 6.8-7.4) [20,45,47,48]. Likewise, episodic acidifying events may cause short-term loss of chemosensory abilities in freshwater fish.…”
Section: Ecological Effects Of Acidification On Olfaction (A) Freshwamentioning
confidence: 91%
“…Elvidge presented wild juvenile Atlantic salmon with realistic model predators (visual cues) in a series of streams varying in ambient pH. Previous studies have shown that weakly acidic conditions inhibit the detection and response to conspecific alarm cues by juvenile salmon (Leduc et al 2006). Presumably, salmon in neutral streams have had previous opportunity to assess risk based on the combined visual plus chemical cues, whereas salmon in the acidic streams would not have prior experience with chemical information.…”
Section: Sensory Complementation and Threat-sensitive Learningmentioning
confidence: 99%
“…The occupied sites of twenty individual salmon in each of four streams (neutral: Catamaran Brook and Lower Devil's Brook; acidic: Upper Devil's Brook and Correy Creek; = 40 sites in each stream class), as well as unoccupied nearby control sites ∼1 m directly upstream, were marked with flagged rocks and compared to quantify differences in microhabitat preferences between stream classes. Habitat measurements consisted of pH, temperature ( ∘ C), channel width (m), distance from nearest riverbank (m), shore index (distance from bank/channel width), depth (m), flow rate (m s −1 ) at 50% depth, substrate complexity (described in [15,37]), canopy cover (proportion of the sky directly overhead covered with tree canopy or other vegetation, after [25]), and substrate composition (per cent of area within a 0.5 m radius covered with substrate < 1 cm, 1 cm ≤ < 5 cm, 5 cm ≤ < 15 cm, and ≥15 cm) based on the grain size classes delineated by the Wolman [38] Pebble Count. Physical measures were combined into a multivariate response and analyzed with two-way MANOVA against stream class (neutral or acidic) and fry preference (occupied or unoccupied).…”
Section: Methodsmentioning
confidence: 99%
“…These streams have served as the setting for several earlier studies on the chemically-mediated antipredator behaviours of juvenile salmon that reliably demonstrate differences attributable to the loss of alarm cue function [15,25,27]. The salmon used were exclusively young-of-year (0 + ), hereafter referred to as "fry.…”
Section: Study Sitesmentioning
confidence: 99%
See 1 more Smart Citation